Decreased RNA polymerase III subunit expression leads to defects in oligodendrocyte development - Macintosh, Julia; Michell-Robinson, Mackenzie; Chen, Xiaoru; Bernard, Geneviève (Frontiers in Neuroscience, 2023)
RNA polymerase III (Pol III) is a critical enzymatic complex tasked with the transcription of ubiquitous non-coding RNAs including 5S rRNA and all tRNA genes. Despite the constitutive nature of this enzyme, hypomorphic biallelic pathogenic variants in genes encoding subunits of Pol III lead to tissue-specific features and cause a hypomyelinating leukodystrophy, characterized by a severe and permanent deficit in myelin. The pathophysiological mechanisms in POLR3-related leukodystrophy and specifically, how reduced Pol III function impacts oligodendrocyte development to account for the devastating hypomyelination seen in the disease, remain poorly understood. In this study, we characterize how reducing endogenous transcript levels of leukodystrophy-associated Pol III subunits affects oligodendrocyte maturation at the level of their migration, proliferation, differentiation, and myelination. Our results show that decreasing Pol III expression altered the proliferation rate of oligodendrocytes precursor cells but had no impact on migration. Additionally, reducing Pol III activity impaired the differentiation of these precursor cells into mature oligodendrocytes, evident at both the level of OL-lineage marker expression and on morphological assessment, with Pol III knockdown cells displaying a drastically more immature branching complexity. Myelination was hindered in the Pol III knockdown cells, as determined in both organotypic shiverer slice cultures and co-cultures with nanofibers. Analysis of Pol III transcriptional activity revealed a decrease in the expression of distinct tRNAs, which was significant in the siPolr3a condition. In turn, our findings provide insight into the role of Pol III in oligodendrocyte development and shed light on the pathophysiological mechanisms of hypomyelination in POLR3-related leukodystrophy.